A Socio-Cultural Perspective on Technology for Environmental Sustainability: The Case of Filtering Water Pots (G-filters) in Rajasthan, India - Savage, Timothy (Springer Nature Switzerland, 2024)
The design and adoption of socio-culturally appropriate technologies are critical to addressing the environmental sustainability crisis in the Global South. However, implementing technology-based sustainability initiatives has been shown to be problematic, with many such projects failing to achieve their stated objectives or have any meaningful impact at scale. This is because such endeavours are complex, multifaceted, and interdisciplinary and require a comprehensive understanding of the interplay between tradition, technology, politics, climate, and sustainability. Such projects are also likely to be highly socio-culturally contextual and thus require a deep understanding of the specific context and culture within which they will be built and deployed. This paper presents the results of an ongoing research project in Rajasthan, India, where filtering water pots (G-filters) are used to purify waste-laden water. The water pots are made by the traditional Kumhar potter caste and are used extensively for domestic and agricultural use in the local community. Initial results indicate that these pots fulfil both criteria required for impactful technology-based projects in the Global South; i.e., they are technically effective and socio-culturally appropriate for the context in which they are being used. The paper makes various recommendations based on our findings to date and provides details of the next stages of the project.
Implications of Information and Digital Technologies for Development
18th IFIP Working Group 9.4 Conference on the Implications of Information and Digital Technologies for Development
Keywords: ICT4D, sustainability, technology, water, G-filter, Kumhar, Rajasthan; International Development; Smart & Sustainable Planet; SUSTAINABLE DEVELOPMENT; WATER POLLUTION; Water Treatment